A DFT Study on the One‐Electron Reduction/Oxidation of Biologically Relevant Pteridine Derivatives. Issue 39 (22nd October 2018) - Reibnegger, Gilbert
Abstract: Pteridine derivatives occur ubiquitously in living systems. The biological functions of these nitrogen‐rich heterocyclic compounds remain partly unknown. The most intensively studied role is that of tetrahydrobiopterin as cofactor for the monooxygenases hydroxylating the aromatic amino acids phenylalanine, tyrosine and tryptophan. In these and other reactions pteridine derivatives act as redox catalysts; therefore, their redox behavior is of particular interest. Using density functional theory, one‐electron reduction/oxidation processes involving relevant pteridine derivatives in aqueous solution are studied. For pterins and lumazines, the results reproduce very satisfactorily the experimentally known increasing reductive strength in the order aromatic, dihydro and tetrahydro compound. The influence of simple substituents at different molecular sites is studied. Results on quinoid dihydropterins not only confirm earlier experimental conclusions regarding the structure of these quite instable compounds, they also provide a theoretical rationale why quinoid dihydrobiopterin may have evolved as intermediate in the cofactor role of tetrahydrobiopterin. Abstract : Pteridines occur ubiquitously in living matter as pigments, coenzymes and more. Their redox behavior is of central interest but experimental evidence is rare. Therefore, the one‐electron oxidation/reduction of a variety of characteristic pteridine derivatives is studied by density functional theory technique. The results explain important experimentally observed properties of these molecules. Shown are electron density isosurfaces of pterin (top) and its radical anion (left) / cation (right), colored according to the local electrostatic potential (red, positively; blue, negatively charged regions).